Management of Severe Non Immune Hydrops Fetalis Cases: The Role of Diagnostic and/or Therapeutic Interventions - Beksaç, Mehmet Sinan; Özlü, Tülay; Dikensoy, Ebru; Cebesoy, Bahar (Gynecology Obstetrics & Reproductive Medicine, 2009)
OBJECTIVE: Non-immune hydrops fetalis (NHF) may have a wide variety of etiologies. The prognosis of this condition is generally poor. There are no standard, optimal management strategies and the clinical management presents a dilemma most of the time. STUDY DESIGN: We retrospectively evaluated 8 NHF cases which several intrauterine interventions are performed. We discuss the role of such interventions in NHF cases. RESULTS: In these 8 cases, we performed the three interventional methods (FBS, IUT, and intravenous Sandoglobulin) for NHF. 6 patients of them had hydrops fetalis, one had renal agenesia and hydrops and the other had maternal acute CMV infections. CONCLUSION: These interventions gave us some oppurtunities. For example, the fetus in the first case, could be followed until 35th gestational weeks and was delivered alive. By this way a postnatal diagnosis of galactosialidosis could be possible. Having this information will be useful for the patient when planning the future pregnancies